A community-academic partnership to explore informational needs of African American women as a primer for cancer clinical trial recruitment. Issue 6 (18th August 2019) - Rivers, Desiree A.; Pal, Tuya; Vadaparampil, Susan T.; Adams, Lauren A.; Dash-Pitts, Lolita; Quinn, Gwendolyn P.
ABSTRACT: Background: African Americans (AAs) are less likely to participate in cancer clinical trials (CCTs) despite experiencing disproportionately higher rates of cancer mortality. As a way to address these ongoing disparities, this study sought to qualitatively explore informational needs regarding CCTs among AA women and identify message considerations for educational information targeting AA women and their community. Methods: Three focus groups were conducted in which AA women viewed a DVD created as a decisional tool for CCT participation and provided feedback regarding content. Results: Results indicated general fear regarding CCTs, which is partially attributable to the impact of historic research abuses, lack of information regarding CCTs, and lack of cultural relevance of the education and outreach materials for AA communities. Recruitment of AAs to CCTs may be enhanced by educational and outreach approaches that increase awareness of CCTs as well as involvement of the AA community in developing such interventions. Conclusion: Interventions should include the perspectives of AA women, as key stakeholders and decision-makers for their family and provide research information in a multimedia format that will facilitate family discussion and decision-making regarding CCTs.